Pengaruh Modal Usaha dan Tenaga Kerja Terhadap Pendapatan dengan Kredit sebagai Variabel Moderasi pada Pedagang di Pasar Seni Sukawati - Tri Wiguna, I Nyoman Gede; Widanta, A.A. Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 11, November 2016 (pp. 1168 - 1346), 2016)
Revenues earned in Sukawati Art Market traders is determined by several factors, some of which are capital, labor and credit. This study aimed to analyze the influence of capital and labor to income with a credit as a moderating variable in Art Market Sukawati, Gianyar. In this study using primary data through direct interviews to 89 respondents with a sampling probability proportional to size sampling. Data analysis technique used is the technique of regression moderation through interaction test. The results showed that venture capital and manpower have positive effect on income, credit moderating influence of venture capital on the income, and credit does not have moderate the effect of labor on the income trader at the Art Market Sukawati, Gianyar. Advice can be given in this research is to increase the income trader Sukawati Art Market traders should increase working hours so that the higher the income earned.
Keywords: capital, labor, credit, income